Resynchronizing variable-length codes for robust image transmission - Hemami, S.S.; Chang, T.; Lau, R. (Proceedings DCC'99 Data Compression Conference (Cat. No. PR00096), 1999)
Summary form only given. This paper considers instantaneous prefix codes with possibly unequal codeword lengths but specific codewords, such as a Huffman code. Resynchronizing VLC (RVLC) contain one or more synchronizing codewords that resynchronize the decoder regardless of any previous data. Previous applications of optimal resynchronizing VLC have been limited to sources with alphabets of sizes less than 30, while only non-optimal VLC with ad-hoc marker codewords have been applied to image data. This paper adapts a general design algorithm for optimal resynchronizing VLC to JPEG image data, demonstrating its applicability to sources with large alphabets (>1000). In order to ensure that the decoded data is placed properly in the image following resynchronization, the resulting VLC are modified to contain extended synchronizing codewords to serve as markers. Minor modifications to the baseline JPEG coder increase the robustness to errors, and a concealment algorithm locates and repairs errant data. Images coded using the RVLC-JPEG combined with the concealment algorithm are robust to BER as high as 2/spl times/10/sup -4/ and are extremely tolerant of burst errors. The excellent tolerance to both bit and burst errors at high bit rates demonstrates that images coded with such RVLC can be transmitted over imperfect channels suffering bit errors or packet losses without channel coding for the image data. At lower bit rates, while the overhead is non-trivial, the encoded bitstream does not have firm restrictions on numbers or spacings of errors and hence provides more graceful degradation than traditional ECC.